Case Report: A Child With Functional Chronic Duodenal Obstruction Caused by Megaduodenum - Qu, Zhibo; Zheng, Biao; Ju, Chuncheng; Liu, Jiaxu; Liu, Bingyang; Zhang, Haoran (Frontiers in Pediatrics, 2021)
Megaduodenum is a clinical syndrome which is characterized by the remarkable expansion of duodenum. Megaduodenum can be caused by mechanical or functional chronic duodenal obstruction. Functional chronic duodenal obstruction of megaduodenum in children is a clinical syndrome characterized by non-mechanical obstruction of the duodenum and marked expansion. It is an extremely rare congenital disease. Our paper report a 1-year-old girl with functional chronic duodenal obstruction caused by megaduodenum.